Face-saving and Seasonal Gifts: Analysis of Cultural Exchanges in the Confucian Market Place - Benuyenah, Vic (International Review of Management and Marketing, 2021)
Contrasting views on whether gifts are undervalued or overvalued have featured in the Western literature. Most previous studies point to gift undervaluation, which leads to receivers re-gifting or returning what they have received from their loved ones. This study takes the discussion further by investigating the existence of Deadweight Loss (DWL) in gifts received during Valentine’s Day. The study finds no evidence of DWL in the assessment of gifts, although, face-saving plays a role in the evaluation of cash-gifts. The absence of DWL in the valuation of gifts significantly implies that post-purchase returns of unwanted gifts are unlikely in the context of Vietnamese Valentine’s gifts. Keywords: face-saving, Vietnam economy, psychological marketing, Valentine gifts, Lunar New Year JEL Classifications: M2, M3, D91 DOI: https://doi.org/10.32479/irmm.11202